The Genitourinary Pathology Society Update on Classification of Variant Histologies, T1 Substaging, Molecular Taxonomy, and Immunotherapy and PD-L1 Testing Implications of Urothelial Cancers. (July 2021) - Compérat, Eva; Amin, Mahul B.; Epstein, Jonathan I.; Hansel, Donna E.; Paner, Gladell; Al-Ahmadie, Hikmat; True, Larry; Bayder, Dilek; Bivalacqua, Trinity; Brimo, Fadi; Cheng, Liang; Cheville, John; et al.
Abstract : The Genitourinary Pathology Society (GUPS) undertook a critical review of the recent advances in bladder cancer focusing on important topics of high interest for the practicing surgical pathologist and urologist. This review represents the second of 2 manuscripts ensuing from this effort. Herein, we address the effective reporting of bladder cancer, focusing particularly on newly published data since the last 2016 World Health Organization (WHO) classification. In addition, this review focuses on the importance of reporting bladder cancer with divergent differentiation and variant (subtypes of urothelial carcinoma) histologies and the potential impact on patient care. We provide new recommendations for reporting pT1 staging in diagnostic pathology. Furthermore, we explore molecular evolution and classification, emphasizing aspects that impact the understanding of important concepts relevant to reporting and management of patients.